The ER-Mitochondria Interface as a Dynamic Hub for T Cell Efficacy in Solid Tumors - Hunt, Elizabeth G.; Andrews, Alex M.; Larsen, Sydney R.; Thaxton, Jessica E. (Frontiers in Cell and Developmental Biology, 2022)
The endoplasmic reticulum (ER) is a large continuous membranous organelle that plays a central role as the hub of protein and lipid synthesis while the mitochondria is the principal location for energy production. T cells are an immune subset exhibiting robust dependence on ER and mitochondrial function based on the need for protein synthesis and secretion and metabolic dexterity associated with foreign antigen recognition and cytotoxic effector response. Intimate connections exist at mitochondrial-ER contact sites (MERCs) that serve as the structural and biochemical platforms for cellular metabolic homeostasis through regulation of fission and fusion as well as glucose, Ca2+, and lipid exchange. Work in the tumor immunotherapy field indicates that the complex interplay of nutrient deprivation and tumor antigen stimulation in the tumor microenvironment place stress on the ER and mitochondria, causing dysfunction in organellar structure and loss of metabolic homeostasis. Here we assess prior literature that establishes how the structural interface of these two organelles is impacted by the stress of solid tumors along with recent advances in the manipulation of organelle homeostasis at MERCs in T cells. These findings provide strong evidence for increased tumor immunity using unique therapeutic avenues that recharge cellular metabolic homeostasis in T cells.